Computer Modelling of Metal Nanoparticles Adsorbed on Graphene - O. V. Khomenko, A. A. Biesiedina, K. P. Khomenko, and R. R. Chernushchenko (Успехи физики металлов, 2022)
The influence of deposited Al, Pd, Co, Au, Ni atoms on a single-layer graphene substrate is investigated using computer simulations. The computer modelling of spraying nanoparticles on the basis of molecular dynamics method is implemented using the NVIDIA®CUDATM technique. According to the results of model calculations, the general behaviour of the system is investigated. The experiments are performed to study the sputtering of atoms of different metals under different initial conditions of the system. Based on these sprays, the behaviour at the beginning of the interaction of the deposited atoms with the substrate is analysed. The time dependences of the lateral position of nanoparticles’ centre of mass and the substrate force throughout the experiment for different sprayed materials are compared. The behaviour of total and potential energies, temperature and momentum of the system is studied. As shown, there is a jump in total energy and temperature as well as a change in the behaviour of the momentum and the substrate force when carbon atoms of graphene are reached for all depositions.